Internal medicine resident perspectives on scoring USMLE as pass/fail - Sara L. Wallach; Christopher Williams; Robert T. Chow; Nagesh Jadhav; Sapna Kuehl; Jaya M. Raj; Richard Alweis (Greater Baltimore Medical Center, 2020)
Background The scoring rubric on the USMLE Step 1 examination will be changing to pass/fail in January 2022. This study elicits internal medicine resident perspectives on USMLE pass/fail scoring at the national level. Objective To assess internal medicine resident opinions regarding USMLE pass/fail scoring and examine how variables such as gender, scores on USMLE 1 and 2, PGY status and type of medical school are associated with these results. Methods In the fall of 2019, the authors surveyed current internal medicine residents via an on-line tool distributed through their program directors. Respondents indicated their Step 1 and Step 2 Clinical Knowledge scores from five categorical ranges. Questions on medical school type, year of training year, and gender were included. The results were analyzed utilizing Pearson Chi-square testing and multivariable logistic regression. Results 4012 residents responded, reflecting 13% of internal medicine residents currently training in the USA. Fifty-five percent of respondents disagreed/strongly disagreed with pass/fail scoring and 34% agreed/strongly agreed. Group-based differences were significant for gender, PGY level, Step 1 score, and medical school type; a higher percentage of males, those training at the PGY1 level, and graduates of international medical schools (IMGs) disagreed with pass/fail reporting. In addition, high scorers on Step 1 were more likely to disagree with pass/fail reporting than low scoring residents Conclusion Our results suggest that a majority of internal medicine residents, currently training in the USA prefer that USMLE numerical scoring is retained and not changed to pass/fail.